Fermentação em estado sólido de resíduos do processamento de frutas : acerola (Mapighia glabra L.), mangaba (Harconia speciosa) e graviola (Annona muricata) para a obtenção de compostos bioativos - Lima, Juliana dos Santos (2014)
The fruit waste due to the high nutritional content, have the potential to be used fresh or as substrate in biotechnological processes. The solid state fermentation (SSF) has been identified in recent years as an effective strategy for bioactive compounds from agroindustrial residues. In this context, the aim of this work was to evaluate the potential use of waste acerola (Malpigia glabra) mangaba (Harconia speciosa) and soursop (Annona muricata) as substrate for the production of bioactive compounds (phenolics and flavonoids) from SSF with Aspergillus niger. Initially various solvents were tested for extraction of compounds in fruit waste, and selected acetone at 80%. Among the waste, acerola showed a higher content of phenolic compounds and flavonoids, but because of the lack of adaptation of the micro-organism to the residue, the fermentations were carried out with the residue of soursop varying the temperature and humidity of residue according experimental design central composite rotational. The SSF of soursop residue resulted in higher total phenolic compounds concentration than the obtained on unfermented waste, when used fermentation temperature of 40 ° C and humidity of 30% residue at 120 h of fermentation. However, the greatest antioxidant capacity was obtained when using temperature at 30°C and 50% humidity of residue. In the fermented 2 (47 ° C Temperature / Humidity 36% residue), 5 (30 ° C Temperature / Humidity residue of 50%), 7 (Temperature 40 ° C / humidity 30% of the residue) and 8 (temperature 40 ° C / humidity 70% of the residue) which showed higher concentrations of phenolic compounds and flavonoids, the protocatechuic acid compound, not present in the unfermented soursop residue, was identified. An unidentified compound was detected in fermented 8 with highest concentration than that obtained in the unfermented soursop residue. Consequently, the soursop residue showed potential to be used as substrate for the production of bioactive compounds in solid state fermentation, making it an interesting alternative for future industrial applications.